COVID-19 knowledge, attitude and awareness among preclinical and clinical dental students: An online-based cross-sectional survey - Saqib Ali; Saman Tauqir; Beenish Fatima Alam; Faraz Farooqi; Asim Mustafa Khan; Abdul Khabeer (Journal of Oral Research, 2021)
Objective: The aim of this study was to assess the understanding and perception of Coronavirus Disease 2019 (COVID-19) among the undergraduate preclinical and clinical dental students within Pakistan. Material and Methods: An online survey was developed by the researchers and conducted amongst the undergraduate students at various dental colleges of Pakistan. A pretested questionnaire was used and distributed using social media platforms. The questionnaire consisted of demographics, health status, perception related to general hygiene, understanding and learning attitudes of dental students. Knowledge scores and the attitude responses were compared with the demographics using independent t-test, one-way ANOVA and chi-square, as appropriate. Results: A total of 800 undergraduate dental students responded to the survey, out of which 304(38%) were males and 496(62%) were female students. Students in pre-clinical years were 600(75%), while 200(25%) students were in the clinical years. The knowledge of clinical students regarding COVID-19 was statistically higher (4.71/6), compared to the students in pre-clinical years (4.49/6) (p=0.004). Both groups showed adequate knowledge regarding the route of transmission, symptoms, and origin of COVID-19, and COVID-19 being a threat to life. Clinical students did not want to re-use the face mask (75%), compared to the preclinical students (68%) (p-0.048). Students in clinical years reported more awareness regarding the recommended handwashing technique during COVID-19 (p-<0.001). Conclusion: It can be concluded that dental students in clinical years have adequate knowledge regarding the COVID-19 as compared to the preclinical students. The study identifies all areas where preclinical and clinical students lack basic knowledge. This should be compensated by arranging different webinars and online courses to increase the understanding of both clinical and preclinical students during the pandemic.